1999
DOI: 10.1051/aas:1999183
|View full text |Cite
|
Sign up to set email alerts
|

AGNs with composite spectra

Abstract: Abstract. In a previous paper (Véron et al. 1997) we presented medium resolution (3.4Å F W HM) spectroscopic observations of 15 "transition objects", selected for having an ambiguous location in the Veilleux & Osterbrock (1987) diagnostic diagrams, and showed that most of them were in fact "composite", this being due to the simultaneous presence on the slit of both a Seyfert or Liner nucleus and a H ii region. Here, we report new spectroscopic observations of 53 emission-line galaxies with a "transition" spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 124 publications
7
69
0
1
Order By: Relevance
“…The type 1 AGN nature of the nucleus was already reported by Sanders et al (1988). Farrah et al (2003) found that this system is a composite object containing both starburst and AGN contributions, consistent with the result for its optical spectrum (Goncalves et al 1999). New evidence come from radiofrequencies where it is found a compact nucleus with flat spectral shape (Baan & Klockner 2006).…”
Section: Ugc 05101 (Iras 09320+6134)supporting
confidence: 81%
“…The type 1 AGN nature of the nucleus was already reported by Sanders et al (1988). Farrah et al (2003) found that this system is a composite object containing both starburst and AGN contributions, consistent with the result for its optical spectrum (Goncalves et al 1999). New evidence come from radiofrequencies where it is found a compact nucleus with flat spectral shape (Baan & Klockner 2006).…”
Section: Ugc 05101 (Iras 09320+6134)supporting
confidence: 81%
“…A result consistent with this scenario is the spettroscopic discovery in the nuclear region of 4C 26.42 of two clouds with a difference velocity of ∼330 km s −1 . Their emission line ratios of Hα and Hβ are very similar and typical of Liners exceptionally weak O [III] lines (Gonçalves et al 1999). However, no clear evidence of rotating gas has been found.…”
Section: Discussionmentioning
confidence: 68%
“…For example, Mazzarella et al (1991); Riffel et al (2006) classified this source as a SB. Yet, according to Gonçalves et al (1999), its optical nuclear spectrum is not only starburst-dominated, but also hosts a Seyfert 2 (Sy 2) nuclei. In fact, many studies have classified this source as a Sy 2 (e.g.…”
Section: Sample and Previous Stellar Population Studiesmentioning
confidence: 99%